Community Empowerment in the Development of Community-Based Tourism at Manggar Baru Village, Balikpapan City - hidayanti Hu; Enos Paselle; Cathas Teguh (Indonesian Journal Publisher, 2026)
This study explores the process of community empowerment in the development of community-based tourism in Manggar Baru Village, Balikpapan City, with the aim of understanding the dynamics of participation, identifying supporting and hindering factors, and analyzing its implications for sustainable local welfare. Using a quantitative research approach, data were collected through structured questionnaires, observations, and documentation from local residents, members of Tourism Awareness Groups (Pokdarwis), and tourism stakeholders. The analysis employed descriptive and inferential statistical techniques, including correlation and regression, to examine the relationships between empowerment variables such as access to resources, leadership, social networks, and participation levels. The findings reveal that empowerment has encouraged local entrepreneurship, strengthened social cohesion, and fostered environmental awareness, yet remains constrained by limited financial capacity, bureaucratic rigidity, and unequal resource access. Overall, the study concludes that sustainable community-based tourism can only be achieved through participatory governance, inclusive policy support, and continuous capacity building that enhances community autonomy and resilience.